PKM Application of Science and Technology for Waste Processing, Digital Marketing and Accounting in Sanphora Village, Tangerang - Wiwit Suprihatiningsih; I G. Ayu Arwati; Erna S. Imaningsih; Muhammad Fikri; Arip Setiawan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Tanggerang district government, Banten, has established a waste bank program so that waste can have economic value and residents do not throw it away carelessly. From data recorded at the Tangerang City Environmental Service (DLH), there are 361 operating waste bank points. In Sanphora village, especially Cilandak Baru village number 114, RT 04, RW 04. Based on the results of a survey by a team of lecturers and students after meeting with the head of RT 04 named Mr. Sutarman and his wife who served as head of PKK RT 04 named Mrs. Kusmiati with complaints that in the area of Sanpora village there has not been a Waste Bank established, so that a lot of waste is not processed, so that the environment becomes dirty and smells bad, which can cause disease for the residents around it. University and its students through this community service activity will solve the waste problem in Sanphora village in RT04, Tangerang, while this PKM activity will apply appropriate technology to make liquid fertilizer from organic waste, make handicrafts from inorganic waste and introduce simple accounting and digital marketing uses the Smart application to sell PKM products, where it is hoped that the products produced from this activity can be sold so as to improve the standard of living of PKK mothers, especially in RT 04 in Sanphora Village, Tangerang. Keywords: Waste Bank, Appropriate technology, Smart Applications